Didactic unit production process and the UNESCO framework as a reference for teaching materials development (Revista Electrónica Calidad en la Educación Superior, 2020)
The path traveled by university’s press in Latin America and the Caribbean has been consolidated, as have the organizations that promote its development and the didactic production; therefore, this paper speaks out this journey, its contributions and also, the theoretical framework. Specifically, this research focused on contrasting the didactic unit’s production process by the Programa de Producción de Materiales Didácticos (PROMADE) of the Universidad Estatal a Distancia (UNED) of Costa Rica with the UNESCO framework, as a theoretical reference for the of the teaching materials elaboration. The results indicate that the PROMADE process agrees with the selected theoretical reference, in addition, its material production contributions over the past 16 years are highlighted. We concluded that the PROMADE production process fulfills a mature cycle, whose characteristic allows it to apply quality standards that could be plotted. Improvement opportunities are also identified, including marketing and sales.
Keywords: Standardization; distance education; higher education; didactic unit; teaching materials